MicroRNA‐206 inhibits influenza A virus replication by targeting tankyrase 2. (4th November 2020) - Bamunuarachchi, Gayan; Yang, Xiaoyun; Huang, Chaoqun; Liang, Yurong; Guo, Yujie; Liu, Lin
Abstract: Due to the frequent mutations, influenza A virus (IAV) becomes resistant to anti‐viral drugs targeting influenza viral proteins. There are increasing interests in anti‐viral agents that target host cellular proteins required for virus replication. Tankyrase (TNKS) has poly (ADP‐ribose) polymerase activity and is a negative regulator of many host proteins. The objectives of this study are to study the role of TNKS2 in IAV infection, identify the microRNAs targeting TNKS2, and to understand the mechanisms involved. We found that TNKS2 expression was elevated in human lung epithelial cells and mouse lungs during IAV infection. Knock‐down of TNKS2 by RNA interference reduced viral replication. Using a computation approach and 3′‐untranslation regions (3′‐UTR) reporter assay, we identified miR‐206 as the microRNA that targeted TNKS2. Overexpression of miR‐206 reduced viral protein levels and virus production in cell culture. The effect of miR‐206 on IAV replication was strain‐independent. miR‐206 activated JNK/c‐Jun signalling, induced type I interferon expression and enhanced Stat signalling. Finally, the delivery of an adenovirus expressing miR‐206 into the lung of mice challenged with IAV increased type I interferon response, suppressed viral load in the lungs and increased survival. Our results indicate that miR‐206 has anti‐influenza activity by targeting TNKS2 and subsequently activating the anti‐viral state.